(untitled) (Journal of Pharmaceutical Negative Results, 2018)
Background: The need to identify new antimicrobial drugs that present different mechanisms of action is urgent. The variety of biologicalproperties of chalcones give them a potential therapeutic compounds. Chalcones’ synthetic manipulations are investigated worldwide in searchof more powerful and efficient drugs to several infectious diseases’ treatment. Objective: The purpose of this work was to evaluate the potentialantibacterial, antifungal, and anti‑dengue virus(DENV) of new ten triazole chalcones. Materials and Methods: Triazole chalcones were usedto determine its antibacterial activity against Gram‑positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis), Gram‑negativebacteria (Klebsiella pneumoniae, Enterobacter cloacae, Acinetobacter baumannii, and Pseudomonas aeruginosa) species, and anti‑Candidaactivity (Candida albicans) by the broth microdilution assay. The anti‑DENV activity was evaluated by cell viability quantification after viralinfection by 3‑(4,5‑dimethylthiazol‑2‑yl)‑2,5‑diphenyltetrazolium bromide colorimetric assay. Results: Although Triazole chalcones haveshown a low cytotoxicity concentration (with CC50 of 47.21–192.51 µg/mL), these compounds did not exhibit antimicrobial activity againstGram‑negative and Gram‑positive bacteria, C. albicans neither DENV, even in the highest concentration tested. Triazole chalcones had no activityagainst all tested microorganisms, except for Gram‑positive S. epidermidis bacteria when a poor antimicrobial effect was observed (125 µg/mL). Conclusion: The results suggest that triazole chalcones investigated in this study are not promising antimicrobial agents.